Access to Boarding Secondary Schools in Uganda: the Extent of the Exacerbation of Social Inequalities - Christian Kakuba; Marc Pilon (Cahiers de la Recherche sur l'Education et les Savoirs)
In 2007, Uganda became one of the first countries in Sub-Saharan Africa to implement universal secondary education. This increased access, but in 2010, 70% of secondary schools were privately owned and 41% of public schools were boarding schools. Boarding schools have a good reputation in Uganda for academic performance compared with day schools. We used Uganda National Household Survey data for 2005/2006 and 2009/2010 to measure inequalities and trends in access to boarding schools. Our findings indicate that the policy has failed to resolve the existing inequalities, as children of the poor, children who are not related to the head of household and children living with an unmarried head of household had less chance of being boarders both before and after the policy was implemented. Additionally, the fact that more parents from the poorer Northern region continue to place their children in boarding facilities is due more to the government’s failure to build day secondary schools.